Calcium Handling in hiPSC-Derived Cardiomyocytes - Yee-Ki, Lee.; Chung-Wah, Siu.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
NA
Calcium is crucial in governing contractile activities of myofilaments in cardiomyocytes, any defeats in calcium homeostasis of the cells would adversely affect heart pumping action. The characterization of calcium handling properties in human induced pluripotent stem cell-derived cardiomyocytes (iPS-CMCs) is of significant interest and pertinent to the stem cell and cardiac regenerative field because of their potential patient-specific therapeutic use. Table of contents: Myocardial Infarction and Heart Failure -- Embryonic Stem Cells/ Pluripotent Stem Cells -- Human Induced Pluripotent Stem Cell (hiPSC)-derived Cardiomyocytes as a Source for Cardiac Regeneration -- Calcium Homeostasis in Cardiomyocytes -- Sarcoplasmic Reticulum (SR) Governs Maturity of Cardiomyocytes -- SR Junctional Proteins Play a Role in Calcium Flux Between Cytosol and SR -- Spatial and Temporal Ca2+ Wavefront Dictated by T-tubule Structure -- IP3-Mediated Calcium Release Contributes to Whole-Cell Calcium Transients -- Calcium Handling Properties of hES-derived Cardiomyocytes -- iPSC-derived Cardiomyocyte as A Potential Platform for Disease Modellig of Impaired Calcium-Handling Related Syndrome -- Measurement of Cytosolic [Ca2+] by Fluorescence Confocal Microscopy -- Excitation-Contraction (EC) Coupling Assessment -- Limitation and Future Studies.
Keywords: Life sciences; Cardiology; Cytology; Stem cells; Life Sciences; Stem Cells; Cardiology; Cell Biology